Animal Design Through Functional Dietary Diversity for Future Productive Landscapes - Beck, Matthew R.; Gregorini, Pablo (Frontiers in Sustainable Food Systems, 2021)
Pastoral livestock production systems are facing considerable societal pressure to reduce environmental impact, enhance animal welfare, and promote product integrity, while maintaining or increasing system profitability. Design theory is the conscious tailoring of a system for a specific or set of purposes. Then, animals—as biological systems nested in grazing environments—can be designed in order to achieve multi-faceted goals. We argue that phytochemical rich diets through dietary taxonomical diversity can be used as a design tool for both current animal product integrity and to develop future multipurpose animals. Through conscious choice, animals offered a diverse array of plants tailor a diet, which better meets their individual requirements for nutrients, pharmaceuticals, and prophylactics. Phytochemical rich diets with diverse arrangements of plant secondary compounds also reduce environmental impacts of grazing animals by manipulating the use of C and N, thereby reducing methane production and excretion of N. Subsequently functional dietary diversity (FDD), as opposed to dietary monotony, offers better nourishment, health benefits and hedonic value (positive reward increasing “liking” of feed), as well as the opportunity for individualism; and thereby eudaimonic well-being. Moreover, phytochemical rich diets with diverse arrangements of plant secondary compounds may translate in animal products with similar richness, enhancing consumer human health and well-being. Functional dietary diversity also allows us to design future animals. Dietary exposure begins in utero, continues through mothers' milk, and carries on in early-life experiences, influencing dietary preferences later in life. More specifically, in utero exposure to specific flavors cause epigenetic changes that alter morphological and physiological mechanisms that influence future “wanting,” “liking” and learning of particular foods and foodscapes. In this context, we argue that in utero and early life exposure to designed flavors of future multifunctional foodscapes allow us to graze future ruminants with enhanced multiple ecosystem services. Collectively, the strategic use of FDD allows us to “create” animals and their products for immediate and future food, health, and wealth. Finally, implementing design theory provides a link between our thoughtscape (i.e., the use of FDD as design) to future landscapes, which provides a beneficial foodscape to the animals, an subsequently to us.